Comparison of complication rates for unilateral and bilateral percutaneous nephrolithotomy (PCNL) using a modified Clavien grading system. (29th October 2012) - Kadlec, Adam O.; Greco, Kristin A.; Fridirici, Zachary C.; Hart, Spencer T.; Vellos, Ted G.; Turk, Thomas M.
Abstract : What's known on the subject? and What does the study add? Standardised complication reporting for urological procedures has been encouraged. Percutaneous nephrolithotomy (PCNL) has an acceptably low complication rate, with high‐grade complications being rare. A recent review shows that complication rates for PCNL vary from 15% to 60%, but the Clavien system has not been used in all studies. Also, no study has directly compared unilateral and bilateral procedures. In a direct comparison retrospective study, we showed that bilateral procedures had a higher overall complication rate and suggest that this is probably due to an increased number of percutaneous tracts. OBJECTIVE: To compare complication rates of unilateral vs bilateral percutaneous nephrolithotomy (PCNL) using the modified Clavien grading system. PATIENTS AND METHODS: Single‐institution retrospective chart review. Identified patients who had synchronous bilateral PCNL (B‐PCNL) over an 11‐year period (2000–2011). B‐PCNL patients were matched by age, gender, and stone burden per renal unit with patients who underwent unilateral PCNL (U‐PCNL) over the same period. Complications were recorded and classified using the modified Clavien classification system, and then compared with a two‐sided chi‐square test of proportions. RESULTS: In all, 47 B‐PCNL patients [mean (range) age 54 (14–84) years] and 78 U‐PCNL patients [mean (range) age 54 (17–91 years] were compared. The mean (range) stone burden per renal unit was 2.8 (0.7–7.0) cm and 2.9 (0.7–9.0) cm, respectively. The overall complication rate was higher for B‐PCNL (53.2% vs 30.8%, P = 0.013). Rates of Grade I and Grade II complications trended toward being higher in the B‐PCNL group. Low‐grade complications (Grade I and II combined) occurred more often in the B‐PCNL group ( P = 0.011); the most common low‐grade complication was fever. Two procedures terminated for poor visualisation due to bleeding were successfully completed in delayed fashion with no transfusion and were classified as Grade I complications. There were equivalently low rates of Grade III complications. There were no Grade IV or V complications. CONCLUSIONS: B‐PCNL carries a higher overall complication rate than U‐PCNL when the modified Clavien system is used for classification. Patients undergoing U‐PCNL who have more than one tract dilatation have a higher complication rate than those who have only one tract dilatation. High‐grade complications are uncommon for both procedures.